2021
DOI: 10.1136/thoraxjnl-2020-215838
|View full text |Cite
|
Sign up to set email alerts
|

Ambient PM2.5exposure and hospital cost and length of hospital stay for respiratory diseases in 11 cities in Shanxi Province, China

Abstract: BackgroundFew studies have examined the effects of ambient particulate matter with an aerodynamic diameter less than or equal to 2.5 μm (PM2.5) on hospital cost and length of hospital stay for respiratory diseases in China.MethodsWe estimated ambient air pollution exposure for respiratory cases through inverse distance-weighted averages of air monitoring stations based on their residential address and averaged at the city level. We used generalised additive models to quantify city-specific associations in 11 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…A number of risk factors concerning the occurrence of COPD have been well documented, including genetics, smoking, occupational exposure, chronic asthma, and so on [4]. An increasing body of studies have also indicated that air pollution is an important risk factor of COPD, especially particulate matter with an aerodynamic diameter smaller than 2.5 μm (PM 2.5 ) [5][6][7]. By contrast, physical activity (PA) has been shown as an effective measure to prevent non-communicable diseases, including COPD [8].…”
Section: Introductionmentioning
confidence: 99%
“…A number of risk factors concerning the occurrence of COPD have been well documented, including genetics, smoking, occupational exposure, chronic asthma, and so on [4]. An increasing body of studies have also indicated that air pollution is an important risk factor of COPD, especially particulate matter with an aerodynamic diameter smaller than 2.5 μm (PM 2.5 ) [5][6][7]. By contrast, physical activity (PA) has been shown as an effective measure to prevent non-communicable diseases, including COPD [8].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of COPD is complicated and involves multiple factors such as genetics, lifestyle and environmental exposures (Ni et al 2020, Sadhra et al 2020, Singanayagam &Johnston 2020, Tian et al 2020. Compelling epidemiologic studies suggested that particulate matter (PM) air pollution is an important environmental risk factor for COPD (Cao et al 2021, Park et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small particle size and large specific surface area of ambient PM 2.5 , it can enter the respiratory tract or be deposited in the alveoli, causing respiratory system damage and increasing the incidence of disease ( 15 - 17 ). Each 10 μg/m 3 increase in PM 2.5 (lag0 day) was associated with a 0.34% increase in the risk of hospitalization for respiratory diseases (including pneumonia, acute bronchitis, upper respiratory tract infection, chronic obstructive pulmonary disease, and bronchiectasis) in 252 cities in China ( 15 ); and each 10 μg/m 3 increase in moving average PM 2.5 (lag0–2 days) was associated with a 0.31% increase in the risk of hospitalization for pneumonia ( 16 ).…”
Section: Introductionmentioning
confidence: 99%